The relationship between the quality of life diabetic patients with family function and social support at the Endocrine Polyclinic of the Dr. Zainoel Abidin Regional General Hospital (RSUDZA), Banda Aceh - Maha, Inike Gujamela; Yani, M.; Juwita; Salawati, Liza; Syahrizal; Muhammad Antor Riady; Agus Hendra Al Rahmad (Indonesian Journal of Biomedicine and Clinical Sciences, 2025)
Diabetes mellitus (DM) is a chronic, non-communicable disease that affects patients quality of life (QoL), which can be influenced by family function and social support. This study aimed to evaluate the relationship betweenfamily function social support, and QoL of patients with DM at the Endocrine Polyclinic of RSUDZA Banda Aceh. This was an analytical observational study with a cross-sectional design, employing convenience sampling methods of 96 respondents and using self-report instruments. Data were analyzed using the Spearman test at a 95% confidence interval and α=0.05. The results showed that 86.2% of respondents had good family function, 72.9% had good social support, and 82.3% had a good QoL. There was a significant relationship between familyfunction, social support, and quality of life (p<0.05). In conclusion improving family functioning and social support may enhance the QoL of patients with DM.